1992
DOI: 10.1177/0148607192016002152
|View full text |Cite
|
Sign up to set email alerts
|

Energy Substrate for Liver Regeneration After Partial Hepatectomy in Rats: Effects of Glucose vs Fat

Abstract: This study evaluated the effects of glucose or fat on liver regeneration after partial hepatectomy in rats. Partial hepatectomy with resection of the median and left lateral lobes (67.31%) was performed on three rat groups. Two groups were infused with high-glucose (HG) or high-fat (HF) solutions intravenously 2 days before surgery. The control (C) group was allowed to eat instead of receiving intravenous infusions. Another group with sham operation only was also allowed to eat. Rats were killed 6, 24, 48, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…We found that protein levels of SIRT1 are significantly increased in the livers of young mice at 36 and 48 hours after partial hepatectomy, but SIRT1 is not elevated in livers of old mice after PH. One of the important liver functions after PH is the support of blood glucose levels,19 as glucose is an essential source for the promotion of liver regeneration 20. We found that glucose and TG levels are reduced in old and young mice at 24 hours after PH; however, the reduction of glucose and TGs in old mice is much deeper (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…We found that protein levels of SIRT1 are significantly increased in the livers of young mice at 36 and 48 hours after partial hepatectomy, but SIRT1 is not elevated in livers of old mice after PH. One of the important liver functions after PH is the support of blood glucose levels,19 as glucose is an essential source for the promotion of liver regeneration 20. We found that glucose and TG levels are reduced in old and young mice at 24 hours after PH; however, the reduction of glucose and TGs in old mice is much deeper (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Intracellular energy demand increases during the early PH phases when glycolysis is preferentially utilized for ATP supply by the surviving hepatocytes. Subsequently FFA are the main energy substrate 41 . Accordingly, induction of enzymes isoforms involved in lipid metabolism (e.g., Acaa2, Acads, Hadh, and Echs1) were differentially expressed upon T3 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays an essential role in starvation conditions: in these conditions, cytosol and organelles are delivered to the lysosomes by the up‐regulated autophagic machinery, where they can be recycled and used for critical processes, thus ensuring cell survival (Mizushima et al, 2002; Wang et al, 2001). The first 24 h after PH, for some aspects, resemble a starvation condition for the liver; mitochondrial oxidative energy metabolism is significantly damaged, as revealed by the decrease in the respiratory control index and in the rate of oxidative phosphorylation (Guerrieri et al, 1995); the glycogen stores are depleted both in the periportal and the pericentral areas (Figures 3 and 4; Van Noorden et al, 1994), and the hepatocytes are forced to use anaerobic glycolysis to supply energy to the cells (Lai et al, 1992), particularly in the periportal area (Van Noorden et al, 1994), where we show an increase in free ribosomes (an index of full cell activity). This metabolic condition could induce increases in autophagosomes and lysosomes 24 h after PH in periportal hepatocytes, the cells where proliferation starts and, thus, where the energy demand for biosynthetic processes is higher after PH.…”
Section: Discussionmentioning
confidence: 99%